Competence need satisfaction in language learning (and beyond): Current state of the evidence and directions for exploration - Oga-Baldwin, W. L. Quint; Ryan, Richard M. (Studies in Second Language Learning and Teaching, 2025)
According to self-determination theory, the need to experience competence is one of a well-recognized trio of basic psychological needs, alongside the need for autonomy and relatedness. Although often assessed at the activity level, the need for competence is met situationally when learners feel able to understand and affect the world around them. In language learning, this means the feeling of success firstly in the comprehension and then in the use of the new language. This situated, contextual sense of competence helps explain the complex and dynamic development of motivation within the language learner. In this review, we focus on the need for competence as it applies both theoretically and empirically to the study of learning a new language. Building on scholarship showing that competence need satisfaction is a powerful correlate of motivation in education generally, we survey the evidence for competence need satisfaction as a specific predictor of language learning motivation and achievement, with directions for future exploration. We present a thought experiment for new methods and approaches to the measurement of competence in classrooms.